Raport Projektu NetQues for Speech and Language Therapy Education in Europe - Przybyla, Olga (Logopedia Silesiana, 2015)
The NetQues Project Report Speech and Language Therapy Education in Europe is to present Benchmarks and Key Subject specific and generic Competencies which form common Standards for European SLT initial education for Speech and Language Therapy Education in Europe